Cost of Information and Communications Technology: Essential for Nigeria Social Change and Economic Development. - Ukpe, Emmanuel; S.M.F.D, Syed Mustapha (2014)
The relationship between Information and Communications Technology (ICT) supported system and economic development of a developing country has been documented by several studies [1], [2], [3]. Studies indicated that ICT can significantly and positively impact development and economic landscape of Nigeria if deployed. For many years, Nigerian government and businesses have been investing in Information and Communication Technologies (ICT) as a strategy for promoting development (Author Observed). This strategy has increased demands on Nigerian government to invest both human and energy resources into the development and expansion of ICT infrastructures. This paper adopted the view that while certain organization cultures are absolutely essential for development other organizational forms are not as critical. This paper focuses on to those organizational cultures which are critical for development, such as IT adoption, diffusion and usage as well as impact of IT on Nigeria economic growth.